Brand Consciousness Among Young Office Goers - Sharma, Ajay (International Journal of Psychosocial Rehabilitation, 2019)
Brands are often a ruse to define a person. The younger generation often thinks that their fashion choices define them. Well, other than the fact that you have good or bad dressing sense, it doesn’t tell anything about a person. And to be able to judge a person, you would still have to know how they talk, what they talk about, what they believe in and what they don’t believe in. The youth of today can easily be categorized into two groups:1. The group which is brand conscious 2. The group which isn’t.Brand conscious: People who are essentially quite conscious of what they wear and how they wear it are usually the ones who go after quality more than quantity. They prefer their clothes to be unique and perfect, and they do prefer looking classy over boho. There is, however, absolutely nothing wrong with being brand conscious; if you want something, you go get it, but just make sure you’re not spending way too much on a cloth that could have been bought at a much lesser price. All you need to do is keep your eyes open and be sure that you are not being fooled.Not so brand conscious: People who are not conscious about brands prefer to be able to pick up whatever comes their way. Sometimes the coolest things that they own are picked up from a flea market, and that is what is best about such clothes. They can be styled anyway and can be worn anywhere. As long as the person knows how to carry it, they will rock the look no matter what. Such people often go on shopping trips that are comparatively pocket-friendly. Even after all these differences, there are so many things that unite the youth and make them exactly similar!